Analisis Kualitas Air Di Perairan Danau Waren, Tual (Jurnal Pertanian Terpadu, 2025)
Lake Taman Anggrek, also known as Lake Waren, is situated in Tual City, Maluku, and boasts attractive potential in both fisheries and tourism. The quality of the lake water, which affects its ecological function and ecosystem health, is influenced by human activities, both autochthonous and allochthonous. Poor water quality, characterized by low DO and high concentrations of N and P, can cause massive fish kill. The main cause of water quality decline is pollution, which leads to eutrophication. This research is important for monitoring water quality and maintaining ecosystem balance, as well as providing a basis for regulations related to pollution and restoration programs to prevent damage to the lake ecosystem. Observations were conducted for six weeks at Lake Waren, Tual, with samples taken at five stations based on the location of the inlet, outlet, and center of the lake. Physical parameters such as temperature, brightness, and current velocity, as well as other chemical parameters, were measured both in situ and ex situ. The results of the analysis showed that the water quality in Lake Waren was quite good, meeting the standards of PP RI No. 22 of 2021 for fishery activities. The range of physical parameters (temperature 30.9 - 31.25 oC; brightness 2 - 4 m; and current velocity 0.01 - 0.23 m/s) and chemical parameters (DO 5.2 - 5.8 mg/L; pH 7.46 - 8.13; nitrite and nitrate each
Keywords: DO; N and P; Temperature; Waren Lake; Water Quality